Effects of immersive virtual reality-based action observation training integrated with focal muscle vibration on upper extremity in a patient with chronic disability following stroke: a single-subject study - Adamo, Paola; De Leo, Davide; Fava, Tommaso; Binda, Simone; Avanzini, Pietro; Fabbri-Destro, Maddalena; Gatti, Roberto (Physiotherapy theory and practice, 2025)
The association of different sensory inputs enhances brain plasticity in patients after stroke, but no studies have associated Action Observation Training (AOT) delivered in immersive virtual reality (VR) with Focal Vibration (FV) to elicit a kinesthetic illusion coherent with the observed task to improve motor function. The study aimed to evaluate the feasibility of AOT delivered in immersive VR integrated with FV of upper limb muscles on manual dexterity in patients with chronic stroke. A single-subject study was conducted (A-B design). A chronic stroke patient with right spastic hemiparesis underwent a 12-session VR-AOT training consisting of observation and imitation of upper limb transitive tasks. In addition, FV was applied on wrist and finger extensor muscles during observation. Upper limb dexterity was assessed through the Box and Blocks test and kinematic indexes during Nine-Hole Peg Test (NHPT) using an optoelectronic system. The patient underwent three evaluation sessions before treatment (A-phase), three during treatment (B-phase), and a follow-up assessment after 3 months. Change was considered meaningful when two consecutive data points in the treatment period exceeded the baseline two standard deviation range. An improvement in the NHPT score exceeding the minimal detectable change of 32.8 s was found for the paretic upper limb during the B-phase. No differences were found in the Box and Block Test. Benefits induced by integrating VR-based AOT with FV in the current study suggested the need to investigate the effects of this intervention in chronic stroke patients with spasticity.